Maintenance in sustainable stormwater management: issues, barriers and challenges - Knapik, Emma; Brandimarte, Luigia; Usher, Mark (Journal of environmental planning and management, 2025)
There is growing scientific and policy interest towards transitioning from conventional to sustainable systems to manage stormwater in urban areas. The literature has produced several contributions to prove the (often compound) benefit of nature-based solutions (NBS) and discussed challenges to their implementation. However, an open gap remains regarding NBS maintenance over time and how this might hinder a broad uptake. We conducted a comprehensive literature review of academic and technical documents that reveals five significant barriers linked to maintenance that might constitute an obstacle to the transition from grey to green approaches: importance of local context, unclear management responsibilities, lack of funding and incentives, uncertainty regarding long-term costs and performance, and mixed perceptions about maintenance requirements. The analysis also showed how maintenance is more a governance than a technical challenge, and we argue that this arises from its multi-disciplinary knowledge base, increased system complexity and competing policy imperatives.